Local Grid Refinement in New Zealand's Earth System Model: Tasman Sea Ocean Circulation Improvements and Super‐Gyre Circulation Implications. (28th June 2020) - Behrens, Erik; Williams, Jonny; Morgenstern, Olaf; Sutton, Phil; Rickard, Graham; Williams, Michael J. M.
Abstract: This paper describes the development of New Zealand's Earth System Model (NZESM) and evaluates its performance against its parent model (United Kingdom Earth System Model, UKESM) and observations. The main difference between the two earth system models is an embedded high‐resolution (1/5°) nested region over the oceans around New Zealand in the NZESM. Due to this finer ocean model mesh, currents such as the East Australian Current, East Australian Current Extension, Tasman Front, and Tasman Leakage, and their volume and heat transports are better simulated in the NZESM. The improved oceanic transports have led to a reduction in upper ocean temperature and salinity biases over the nested region. In addition, net transports through the Tasman Sea of volume, heat and salt in the NZESM agree better with previously reported estimates. A consequence of the increased cross‐Tasman Sea transports in the NZESM is increased temperatures and salinity west of Australia and in the Southern Ocean reducing the meridional sea surface temperature gradient between the subtropics and sub‐Antarctic. This also leads to a weakening of the westerly winds between 60°S and 45°S over large parts of the Southern Ocean, which reduces the northward Ekman transport, reduces the formation of Antarctic Intermediate Water, and allows for a southward expansion of the Super‐Gyre in all ocean basins. Connecting an improved oceanic circulation around New Zealand to a basin‐wide Super‐Gyre response is an important step forward in our current understanding of how local scales can influence global scales in a fully coupled earth system model. Plain Language Summary: We describe the model development of the New Zealand Earth System Model and assess its performance against the model on which it is based (United Kingdom Earth System Model) and observations. The New Zealand Earth System Model is a fully coupled earth system model, which aims to model all relevant bio‐physical processes in and between the atmosphere, land, ocean, and sea‐ice. The main difference between both models is that the oceans around New Zealand in the New Zealand Earth System Model are more precisely modeled, due to a refined ocean model mesh in this region. That results in a more accurate oceanic circulation around New Zealand in the New Zealand Earth System Model compared to the United Kingdom Earth System Model and reduced model biases of temperature and salinity. These oceanic changes have implications beyond the oceans around New Zealand, causing a warming in the Southern Ocean and a related weakening of the westerly winds over the Southern Ocean. This weakening of the winds allows subtropical waters to reach further south into the Southern Ocean. It is notable that regional changes in the ocean circulation can have implications on the global scale. Key Points: NZESM is a nested fully coupled ESM based on UKESM with a high‐resolution ocean grid of 1/5° around New Zealand The oceanic circulation is improved in NZESM over the nested domain and model biases of temperature and salinity are reduced The Super‐Gyre intensifies and expands southward due to wind changes triggered by changes in the large‐scale heat transport